Sustainability Transformations in Higher Education: Global Perspectives on The Challenges and Solutions - Shih, Yi-Huang; Hsu, Meng Chin; Chang, Chung Liang (Ilmu Inovasi Nusantara, 2025)
Higher Education Institutions (HEIs) are critical in addressing global sustainability challenges by fostering transformative change in education, research, and societal engagement. However, the integration of sustainability into higher education remains fraught with challenges, including institutional resistance, limited resources, and a lack of interdisciplinary approaches. These barriers hinder the potential of HEIs to act as catalysts for sustainability transformations. This study aims to explore global perspectives on the challenges faced by HEIs in promoting sustainability and identify innovative solutions to overcome these obstacles. The research adopts a qualitative methodology, synthesizing findings from case studies, policy analyses, and interviews with key stakeholders from HEIs worldwide. By examining successful initiatives and adopting sustainable practices, this study identifies strategies to enhance the contribution of HEIs to the Sustainable Development Goals (SDGs). Findings highlight the importance of fostering collaboration across disciplines, securing institutional commitment, and leveraging technological advancements to mainstream sustainability. HEIs influence not only students' mindsets but also the development of policies, technologies, and societal values. Moreover, their contributions extend beyond education, providing frameworks for global sustainability efforts. The prioritizing holistic sustainability strategies, including integrating sustainability into curricula, promoting stakeholder partnerships, and ensuring long-term institutional support. By addressing these challenges and implementing innovative solutions, HEIs can become pivotal drivers of sustainable development, shaping a future that aligns with the SDGs and inspires collective global action